2006
DOI: 10.1300/j069v25n02_07
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Treatment Patterns in a Novel Methadone Maintenance Clinic Targeting Young Adults

Abstract: This observational study examined the antidepressant treatment patterns of a novel New York City methadone maintenance treatment program (MMTP), founded for the treatment of adolescents and now targeting young adults and older patients with special problems. The goal of the study was to investigate demographic or clinical characteristics that were associated with prescribing patterns, as well as whether antidepressant use was associated with sobriety. The method of data collection was a thorough chart review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Although these signal accomplishments are valuable and widely acknowledged, long-term agonist-based treatments have also been shown to be associated with appreciable mortality rates in both the medium (Brugal et al, 2005) and longer term (Hser et al, 1993;Caplehorn et al, 1996;Caplehorn & Drummer, 1999;Hser et al, 2001;Gibson et al, 2008;Davstad et al, 2009) and to be associated with an immunosuppressive (Pillai et al, 1991;McCarthy et al, 2001;Li et al, 2002;Suzuki et al, 2002;Cabral, 2006) state that includes a compensatory immunostimulation (Reece, 2007a(Reece, , 2007b(Reece, , 2007c(Reece, , 2007d, which may mollify with time (Novick et al, 1989;Ochshorn et al, 1989) to suppress cell replication (Zagon et al, 2002) and likely stem cell division (Reece & Davidson, 2007) and particularly affects the brain (Eisch & Harburg, 2006;Canales, 2007;Drake et al, 2007;Kolodziej et al, 2008). Addiction to various drugs including opiates has also been shown to be associated with a number of other changes such as osteoporosis (Kim et al, 2006), hair graying (Reece, 2007b), neuropsychiatric deficits (Dyer & White, 1997;Galarneau et al, 2006;Reece, 2008aReece, , 2008bReece, , 2008cSchreiber et al, 2008), and dental abnormalities (Carter, 1978;Fan et al, 2006;Reece, 2007aReece, , 2007bReec...…”
Section: Introductionmentioning
confidence: 99%
“…Although these signal accomplishments are valuable and widely acknowledged, long-term agonist-based treatments have also been shown to be associated with appreciable mortality rates in both the medium (Brugal et al, 2005) and longer term (Hser et al, 1993;Caplehorn et al, 1996;Caplehorn & Drummer, 1999;Hser et al, 2001;Gibson et al, 2008;Davstad et al, 2009) and to be associated with an immunosuppressive (Pillai et al, 1991;McCarthy et al, 2001;Li et al, 2002;Suzuki et al, 2002;Cabral, 2006) state that includes a compensatory immunostimulation (Reece, 2007a(Reece, , 2007b(Reece, , 2007c(Reece, , 2007d, which may mollify with time (Novick et al, 1989;Ochshorn et al, 1989) to suppress cell replication (Zagon et al, 2002) and likely stem cell division (Reece & Davidson, 2007) and particularly affects the brain (Eisch & Harburg, 2006;Canales, 2007;Drake et al, 2007;Kolodziej et al, 2008). Addiction to various drugs including opiates has also been shown to be associated with a number of other changes such as osteoporosis (Kim et al, 2006), hair graying (Reece, 2007b), neuropsychiatric deficits (Dyer & White, 1997;Galarneau et al, 2006;Reece, 2008aReece, , 2008bReece, , 2008cSchreiber et al, 2008), and dental abnormalities (Carter, 1978;Fan et al, 2006;Reece, 2007aReece, , 2007bReec...…”
Section: Introductionmentioning
confidence: 99%
“…In a second study in the same population, we identified the high prevalence of co-morbidity with depression, and therefore further looked into the impact of pharmacotherapy for depression, in addition to conventional behavioral therapy, in reducing relapse to any drug of abuse during opioid agonist treatment. After controlling for demographic and clinical characteristics, we found that pharmacological antidepressant treatment was, in fact, not significantly associated with a reduction in relapse to heroin, cocaine, or other drugs of abuse in this very young population (Galarneau et al, 2006). …”
Section: Other Recent Clinical Research Studiesmentioning
confidence: 78%
“…Several medications have been used alongside buprenorphine and methadone, but with varying effectiveness. Antidepressants in methadone programs were not significantly associated with a reduction in relapse risk (Galarneau et al, 2006). Though memantine did not significantly improve retention, it did significantly improve short‐term treatment with buprenorphine/naloxone for opioid‐dependent young adults by reducing relapse and opioid use (Gonzalez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%